Determinant Factors Affecting Compliance MSME Taxpayers (Case Study of Cipadang Village Community) - Hardini Ariningrum; Irma Nuryana; Dian Eka Saputri (Komunitas Dosen Indonesia, 2024)
Given that taxes represent the primary revenue source in Indonesia, the government places significant emphasis on the tax processing procedure. Micro, Small, and Medium Enterprises (MSMEs) receive a government-borne incentive of 0.5 percent Final Income Tax, underscoring the government's support for this sector. With 64.2 million MSMEs in Indonesia in 2019, comprising 99.99% of all business entities, these taxpayers are exempted from tax remittance up to a specified threshold, with no tax deductions or collections enforced upon their payments. This study endeavors to assess the impact of religiosity, love of money, tax knowledge, taxpayer awareness, tax rates, and tax sanctions on compliance among MSME taxpayers registered in Cipadang Village. Employing a quantitative approach, data is gathered through questionnaires, involving 30 respondents who are MSME taxpayers. This research contributes to the advancement of tax accounting and behavioral accounting research, particularly concerning compliance with tax payments among MSME taxpayers.